Yes, the Composition of the Market Portfolio Matters: The Estimated Cost of Equity. Issue 4 (6th April 2018) - Kamara, Avraham; Young, Lance
Abstract: Market portfolio composition substantially affects the cost of equity estimates. Adding Treasury securities to an equity‐only market portfolio substantially changes both estimated market betas and the estimated market excess return. Though the sign and magnitude of the net impact of these changes are uncertain, they dramatically impact costs of equity for 30 industry portfolios under the Capital Asset Pricing Model (CAPM) and Fama‐French (1993) Three‐Factor Model. The choice of market portfolio proxy is as important as the choice of the pricing model when estimating costs of equity. Similar conclusions hold when we add real estate, corporate debt, and international securities to the market portfolio.